Предмет: Алгебра,
автор: pak0498
Пожалуйста, 1003!!!!!!!!!
Приложения:
![](https://files.topotvet.com/i/b4d/b4d9f55532ff93ace368ab5504dc58da.jpg)
Ответы
Автор ответа:
0
(2/(c-1)+(c+1)(c²+c+1)-(3c²+2c+4)/(c³-1))/(2/(1-c³)
Упростим первый множитель:
(2(c²+c+1)+(c-1)(c+1)-3c²-2c-4)/(c³-1)=(2с²+2с+2+с²-1-3с²-2с-4)/(с³-1)=
=-3/(с³-1).
-3*(1-с³)/(2*(с³-1))=3*(с³-1)/(2*(с³-1)=1,5.
Упростим первый множитель:
(2(c²+c+1)+(c-1)(c+1)-3c²-2c-4)/(c³-1)=(2с²+2с+2+с²-1-3с²-2с-4)/(с³-1)=
=-3/(с³-1).
-3*(1-с³)/(2*(с³-1))=3*(с³-1)/(2*(с³-1)=1,5.
Похожие вопросы
Предмет: Физика,
автор: vadkuz
Предмет: Обществознание,
автор: gusenkoartem
Предмет: Математика,
автор: yanafrantsuzova999
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: Аноним